Image variability and face matching. (November 2022) - Gogan, Taylor; Beaudry, Jennifer; Oldmeadow, Julian
This study investigates whether variability in perceived trait judgements disrupts our ability to match unfamiliar faces. In this preregistered study, 174 participants completed a face matching task where they were asked to indicate whether two ambient face images belonged to the same person or different people (17, 748 total data points). Participants completed 51 match trials consisting of images of the same person that differed substantially on one trait (either trustworthiness, dominance or attractiveness) with minimal differences in the alternate traits. Participants also completed 51 mismatch trials which contained two photos of similar-looking individuals. We hypothesised that participants would make more errors on match trials when images differed in terms of attractiveness ratings than when they differed on trustworthiness or dominance. Contrary to expectations, images that differed in terms of attractiveness were matched most accurately, and there was no relationship between the extent of differences in attractiveness ratings and accuracy. There was some evidence that differences in perceived dominance and, to a lesser extent, trustworthiness were associated with lower face matching performance. However, these relationships were not significant when alternate traits were accounted for. The findings of our study suggest that face matching performance is largely robust against variation in trait judgements.